Climate and surging of Donjek Glacier, Yukon, Canada - William Kochtitzky; Dominic Winski; Erin McConnell; Karl Kreutz; Seth Campbell; Ellyn M. Enderlin; Luke Copland; Scott Williamson; Brittany Main; Hester Jiskoot (Arctic, Antarctic, and Alpine Research, 2020)
Links between climate and glacier surges are poorly understood but are required to enable prediction of surges and mitigation of associated hazards. Here, we investigate the role of snow accumulation, rain, and temperature on surge periodicity, area changes, and timing of surge initiation since the 1930s at Donjek Glacier, Yukon, Canada. Snow accumulation measured in three ice cores collected at Eclipse Icefield indicates that a cumulative accumulation of 15.5 ± 1.46 or 16.6 ± 2.0 m w.e. occurred in the ten to twelve years between each of its last eight surges, depending on ice motion spatiotemporal offset corrections. Although we find consistent snow accumulation between surges, the transient snow line has risen 10.3 m decade−1 vertically since the 1950s, and Burwash Landing weather station records indicate a 0.5°C decade−1 increase in mean annual air temperature since the 1960s. Changes in surface mass balance are accompanied by a consistent surge interval but decreasing surge extent. The three recent surge events initiated in years with the rainiest summers on record. These findings highlight a complex interplay between external (i.e., climate) and internal glacier processes that control surging at Donjek Glacier, with climate having a more direct influence on surge extent than on recurrence interval.